2010
DOI: 10.1063/1.3327004
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural properties and dislocation evolution on a GaN grown on patterned sapphire substrate: A transmission electron microscopy study

Abstract: The microstructural properties of a GaN layer grown on a patterned sapphire substrate (PSS) were studied in detail using transmission electron microscope techniques to determine dislocation and growth behaviors. Regular and uniform recrystallized GaN islands were observed on the protruding pattern. On a flat sapphire surface, the crystallographic orientation relationship of ⟨1¯21¯0⟩GaN on FS//⟨11¯00⟩sapphire and {11¯01}GaN on FS//{12¯13}sapphire existed between the GaN and the substrate. On the other hand, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 18 publications
1
20
0
1
Order By: Relevance
“…The estimated dislocation densities of samples A-C were 2.9 × 10 9 , 2.4 × 10 9 , and 2.2 × 10 9 cm −2 , respectively. As predicted, given the mechanism of lateral overgrowth [14][15][16], decreases in growth area on the NPSS sidewall reduced the number of dislocations originating from the GaN/sapphire interface. EPD counting (data not shown here) revealed reductions from 2.4 × 10 8 (sample A) to 1.1 × 10 8 (sample B) to 4.1 × 10 7 (sample C).…”
Section: Resultsmentioning
confidence: 78%
“…The estimated dislocation densities of samples A-C were 2.9 × 10 9 , 2.4 × 10 9 , and 2.2 × 10 9 cm −2 , respectively. As predicted, given the mechanism of lateral overgrowth [14][15][16], decreases in growth area on the NPSS sidewall reduced the number of dislocations originating from the GaN/sapphire interface. EPD counting (data not shown here) revealed reductions from 2.4 × 10 8 (sample A) to 1.1 × 10 8 (sample B) to 4.1 × 10 7 (sample C).…”
Section: Resultsmentioning
confidence: 78%
“…The coalescence of GaN islands provided a strain relaxation. 44 During the lateral growth of GaN epilayers, TDs originating from the inclined {1-102} facets changed direction to bend toward the nanopatterns and to propagate within the growth plane. Hence, surface pattern throughout the NPSS contributed to the decreased TDDs and the improved crystal quality.…”
Section: B Structural Properties Of Ledsmentioning
confidence: 99%
“…Interestingly, with the appropriate nucleation layer (NL), most GaN grows in the flat regions between cones, though the flat region is a rather small proportion of the whole substrate, no matter what the geometry of the pattern is [ 10 , 11 , 12 ]. However, some GaN would still form small GaN crystals on the cone sidewalls, which may have negative influences on GaN growth [ 13 , 14 ]. In our previous work, we confirmed that small GaN crystals would generate dislocations [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we confirmed that small GaN crystals would generate dislocations [ 15 ]. When using metal organic chemical vapor deposition (MOCVD) to grow AlN or GaN NLs, the influences of small GaN crystals become more noteworthy [ 13 , 14 , 16 ]. Compared to MOCVD-grown AlN or GaN NLs, Li-Chuan Chang et al found that the utilization of ex situ sputtered AlN NLs could suppress GaN nucleation on cones and improve the quality of GaN films on PSSs [ 17 ].…”
Section: Introductionmentioning
confidence: 99%